2009
DOI: 10.1017/s0007114509992637
|View full text |Cite
|
Sign up to set email alerts
|

Administration of loperamide and addition of wheat bran to the diets of weaner pigs decrease the incidence of diarrhoea and enhance their gut maturation

Abstract: The influence of fibre inclusion and transit time regulation on the performance, health status, microbial activity and population, physico-chemical characteristics of the hindgut digesta and intestinal morphology in early weaned pigs were examined. For these experiments, wheat bran (WB) was used as fibre source and loperamide as a drug (LOP) to increase the digesta transit time. In Expt 1, a total of 128 early weaned pigs were randomly distributed in a 2 £ 2 factorial combination of WB inclusion (0 v. 40 g/kg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
10
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 43 publications
6
10
1
Order By: Relevance
“…In both experiments, the digestibility of all nutrients, except for CP, which was not affected, decreased with the inclusion of fiber in the diet, in agreement with most published reports (Hogberg and Lindberg, 2006;Molist et al, 2010;Zhang et al, 2013). Mateos et al (2007) reported also that the inclusion of 2.0% OH in a control diet that contained 6.5% NDF reduced OM digestibility from 87.0 to 85.0% but that CP digestibility was not affected.…”
Section: Influence Of Dietary Fiber Levelsupporting
confidence: 90%
“…In both experiments, the digestibility of all nutrients, except for CP, which was not affected, decreased with the inclusion of fiber in the diet, in agreement with most published reports (Hogberg and Lindberg, 2006;Molist et al, 2010;Zhang et al, 2013). Mateos et al (2007) reported also that the inclusion of 2.0% OH in a control diet that contained 6.5% NDF reduced OM digestibility from 87.0 to 85.0% but that CP digestibility was not affected.…”
Section: Influence Of Dietary Fiber Levelsupporting
confidence: 90%
“…In the present study, concentrations of acetate, propionate, butyrate and total VFA were positively correlated with the apparent total tract digestibility (ATTD) values of insoluble fiber fractions, which agrees with results from numerous studies in which there was a positive relationship between fermentation of insoluble fiber sources and concentration of butyrate in the large intestine [36,37]. The development of prediction equations for fecal VFA concentrations indicated that the digestibility of IDF is the best single variable with which to predict the concentration of VFA in the feces of pigs compared to the apparent total tract digestibility (ATTD) of other fiber components.…”
Section: Discussionsupporting
confidence: 92%
“…Together with the differences in main cereals, the introduction of wheat bran in the UN diets (4.5-2.5%) is remarkable. The inclusion of wheat by-products, such as wheat bran, rich in insoluble NSP, resistant to fermentation, can reduce bowel transit time [8], which could explain some of the changes found. Actually, wheat bran has been reported to reduce pathogen adhesion [56,57] and to promote the Prevotellaceae family [11,58].…”
Section: Discussionmentioning
confidence: 99%
“…Together with in-feed additives, dietary fiber (DF) has gained attention as a strategy to improve the gut health of weanlings [8][9][10][11]. In addition, the use of fibrous by-products has recently gained interest as a means of reducing production costs [12] and diminishing the environmental impact of the agroindustry [13].…”
Section: Introductionmentioning
confidence: 99%